(untitled) (Pubmet, 2022)
Come learn about Bentham Science Open for journals and e-books and get insights about Managing the Open Access Publication Process. This presentation will focus on helping you understand the publication process, from how to submit a scientific paper through to how to manage your interactions with editors and reviewers to maximize your chances of a successful high-impact outcome for your research. As a result of this course learners will understand: ▸ how to effectively submit scientific papers; ▸ write highly effective cover letters; ▸ select effective and suitable reviewers; ▸ ensure your work has the highest possible chance of getting published in your target journal; ▸ how to effectively communicate with editors and what they expect from authors and reviewers, and; ▸ maximize the impact of your research after publication. Course Content The stages of publication: ▸ what editors expect from submissions ▸ navigating formatting requirements ▸ an amazing cover letter – details and selling your work ▸ initial review and how to survive ▸ ensure your papers gets out for peer-review ▸ dealing with peer-review comments, especially those you disagree with ▸ managing your editor ▸ revisions: how to do the most effective job while making the least number of changes ▸ surviving rejection ▸ how to make complaints if you feel unfairly treated